Performance Enhancements of Fully Inkjet-Printing Technology for Antenna-in-Package and Substrate Integrated Waveguides - Yen-Sheng Chen; Sheng-Xue Huang (International Journal of Antennas and Propagation)
A fully inkjet-printing technology is applied to antenna-in-package (AiP) and substrate integrated waveguide (SIW) to enhance the performance of three components, including via holes, wire bonding, and flexible antenna arrays. First of all, earlier studies utilize shorting pins for the conductive pathway in high-density AiP and SIW, but this requires an additional procedure to plate the conductor. We propose a mechanical approach to form a cylindrical hole, plating the surface with silver nanoparticles and realizing the equivalent circuit model of the shorting pin. The proposed approach does not require high alignment sensitivity or the precise control of laser power level. Second, fully inkjet-printed wire bonding is proposed for the system on the package. The proposed technique not only reduces the discontinuity but also enables a fabrication without additional assembly. Third, the proposed technique is implemented for antenna development, which shows desirable performance with reduced fabrication complexity. The proposed technology is validated by microstrip lines, SIWs, SIW cavity slots, and flexible 4 × 4 patch arrays fabricated on various substrates including RO 4003C, polyimide, and polyethylene naphthalate. For comparison purposes, conventional approaches using printed circuit boards are also implemented and tested. The results indicate the generality and capability of the proposed technique.